The Arabic book - Pedersen, Johannes 1883-1977 (Modern classics in Near Eastern studies, 1984)
This long-awaited translation of Johannes Pedersen's Danish work Den Arabiske Bog (1946) describes in vivid detail the production of books in medieval Islam, and outlines the role of literature and scholarship in Islamic society. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.